Potential of turmeric rhizome essential oils against Aedes aegypti larvae - Roselina Panghiyangani; Leni Marlinae; Isnaini Isnaini; Fauzi Rahman (Faculty of Medicine, Universitas Trisakti, 2012)
BACKGROUNDDengue hemorrhagic fever (DHF) has long been a serious health problem in Indonesia, including Kalimantan (Borneo), as is evident from the increased case fatality rate in Banjarbaru city. Synthetic chemical insecticides have frequently been used to eradicate mosquitoes, but are toxic to the body and resistance of adult and larvae mosquito Aedes aegypti has been reported. The present study aims to assess the effect of essential oils of turmeric rhizomes (Curcuma domestica Val) against Aedes aegypti larvaeMethodsThis was an experimental study of post test one group design, performed in two phases, using Aedes aegypti larvae as test organisms. In the first phase, laboratory-reared larvae were used for calculation of the LC50 and LC90, while in the second phase the test organisms were larvae taken from 75 buildings that had been designated based on a preliminary survey in four sub-districts in Banjarbaru city with a high incidence of dengue cases. Probit analysis of was used to calculate LC50 and LC90, and the Kruskal-Wallis test to determine the larvicidal potency of turmeric rhizome essential oils. ResultsThis study demonstrates that turmeric rhizome essential oils effectively killed laboratory-reared Aedes aegypti larvae at an LC50 of 9.239 ppm and an LC90 of 13.565 ppm. The effectiveness of the essential oils of turmeric rhizomes (Curcuma domestica Val.) for killing Aedes aegypti larvae in residential areas was 68%.ConclusionTurmeric (Curcuma domestica Val.) rhizome essential oils can kill Aedes aegypti larvae, are environment friendly and can be used for the control of mosquitoes.